High-brightness high-whiteness high-temperature-resistant modified copolyester material and preparation method thereof
By using specific composition raw material components for esterification and polymerization, a modified copolyester material with high brightness, high whiteness and high temperature resistance was prepared, which solved the problem of color deterioration of PET materials during processing, and achieved the improvement of the high performance and commercial value of the product.
Patent Information
- Application Number
- CN202411786626.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-24
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-25
AI Technical Summary
Existing PET materials are prone to oxidation during polymerization or subsequent processing, resulting in deterioration of product appearance and color and reducing their commercial value.
High-gloss high-white high-temperature modified copolyester material is prepared by esterification and polymerization of raw material components including terephthalic acid, ethylene glycol, isosorbide, 1,4 cyclohexanedimethanol, germanium dioxide, sodium acetate and antioxidants. The antioxidants are phenolic antioxidants and/or phosphite antioxidants. By controlling the addition of germanium dioxide, sodium acetate and antioxidants, the esterification and polymerization conditions are optimized.
It achieves high brightness, high whiteness, high temperature resistance and impact resistance of PET materials, meets the requirements of manufacturing transparent containers or supplies, avoids the problem of color deterioration, and improves the commercial value of the product.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic composite materials, and particularly relates to a high-brightness, high-whiteness, high-temperature-resistant modified copolyester material and a preparation method thereof. Background Art
[0002] Since the invention of PET (polyethylene terephthalate), the improvement of its performance and the promotion of its application have been ongoing. In particular, the research on improving its high temperature resistance and impact resistance has always been a hot topic in academia and industry. At present, the use of 1,4-cyclohexanedimethanol (CHDM) to enhance the impact strength of PET and the use of isosorbide (isophthalic acid glycol) to improve high temperature resistance have become common knowledge in the industry.
[0003] CN142961C discloses a method for preparing terephthalic acid-ethylene glycol-isosorbide and other diols (including 1,4-cyclohexanedimethanol) copolyesters. CN675282B discloses a method for preparing low-color terephthalic acid-ethylene glycol-isosorbide copolyesters. CN04334607B discloses a method for preparing terephthalic acid-ethylene glycol-isosorbide-1,4-cyclohexanedimethanol copolyesters using a zinc-based compound as an esterification catalyst. However, due to the ether bond contained in the molecular structure of isosorbide, it is easily oxidized and cracked and deteriorated during the polymerization process or in the subsequent injection molding and extrusion process, resulting in deterioration of the product appearance and color, thereby reducing its commercial value. In order to overcome this problem, researchers have been looking for new catalysts and processing technologies to improve the performance of PET while maintaining its cost-effectiveness and commercial feasibility. These efforts are aimed at developing PET materials that are resistant to high temperatures, impact-resistant, and color-stable to meet the market demand for high-performance plastics. Summary of the invention
[0004] The present invention aims to overcome the defects of the prior art and provide a high-brightness, high-whiteness, high-temperature-resistant modified copolyester material.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned high-brightness, high-whiteness, high-temperature-resistant modified copolyester material.
[0006] The technical solution of the present invention is as follows:
[0007] A high-brightness, high-white, high-temperature-resistant modified copolyester material is prepared by esterification and polymerization of raw material components including terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate and an antioxidant, wherein the antioxidant is a phenolic antioxidant and / or a phosphite antioxidant.
[0008] The mass ratio of terephthalic acid, ethylene glycol, isosorbide and 1,4-cyclohexanedimethanol is 70-72:13-14:15-16:30-31;
[0009] The added amount of germanium dioxide is 50-500ppm, the added amount of sodium acetate is 10-500ppm, and the added amount of antioxidant is 100-6000ppm.
[0010] In a preferred embodiment of the present invention, the raw material components further include phosphoric acid, which is added in an amount of 10-200 ppm.
[0011] More preferably, the raw material components further include a toner.
[0012] More preferably, the toner includes cobalt acetate, blue oil, red oil and purple oil.
[0013] In a preferred embodiment of the present invention, the phenolic antioxidant includes at least one of antioxidant 1076, antioxidant 1010 and TBHQ; and the phosphite antioxidant is AT626.
[0014] The preparation method of the above-mentioned high-brightness, high-whiteness, high-temperature-resistant modified copolyester material comprises the following steps:
[0015] (1) Place terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide and sodium acetate into a reactor, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0016] (2) After adding an antioxidant to the material obtained in step (1), stirring is continued, and vacuum is applied to carry out polymerization reaction at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and the reaction is stopped.
[0017] The preparation method of the above-mentioned high-brightness, high-whiteness, high-temperature-resistant modified copolyester material comprises the following steps:
[0018] (1) Place terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate, antioxidant and phosphoric acid into a reactor, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0019] (2) Continue stirring the material obtained in step (1), evacuate the mixture, and carry out polymerization reaction at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and then stop the reaction.
[0020] The preparation method of the above-mentioned high-brightness, high-whiteness, high-temperature-resistant modified copolyester material comprises the following steps:
[0021] (1) Place terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate and toner into a reaction kettle, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0022] (2) adding an antioxidant and phosphoric acid to the material obtained in step (1), continuing to stir, evacuating, and polymerizing at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and then stopping the reaction;
[0023] Or include the following steps:
[0024] (1) Put terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate, antioxidant, phosphoric acid and toner into a reaction kettle, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0025] (2) Continue the material obtained in step (1), evacuate the vacuum, and carry out polymerization reaction at 255-265°C until the intrinsic viscosity of the material reaches 0.6-0.7, and then stop the reaction.
[0026] The beneficial effects of the present invention are: the present invention has good color, high temperature resistance, impact resistance, and meets the requirements for manufacturing various transparent containers or products. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0028] In the following embodiments: PTA is specifically CAS#: 100-21-0, EG is specifically CAS#: 107-21-1, isosorbide is CAS#: 52-67-5, and CHDM is CAS#: 105-08-8.
[0029] Comparative Example 1
[0030] This comparative example was carried out in a 30-liter polyester pilot test device, comprising the following steps:
[0031] (1) According to the existing technical scheme, 7110g of PTA, 1327g of EG, 1565g of isosorbide, and 3088g of CHDM were placed in a reactor in sequence, stirred evenly, and then pressurized to 2kg / cm with nitrogen. 2 Then the temperature is raised to 220°C, the reaction starts at about 220°C, and the temperature is gradually raised from 220°C to 255°C for esterification reaction for 240 minutes, until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0032] (2) continuing to stir the material obtained in step (1), and evacuating the mixture to 75 Pa, then gradually raising the temperature to 255° C., and then gradually raising the temperature to 265° C. while maintaining a vacuum degree of 75 Pa, and carrying out a polymerization reaction for 100 min until the intrinsic viscosity of the material reaches 0.536, and then stopping the reaction;
[0033] (3) The material obtained in step (2) is transported to a pelletizer to be cut into slices.
[0034] The obtained slices were analyzed for glass transition temperature (Tg) by differential scanning calorimetry (DSC), their intrinsic viscosity (IV) was measured by Ubbelohde viscometer, and their brightness and color (L, a, b) were analyzed by spectrophotometer. These data are listed in Table 1 for comparison.
[0035] Example 1
[0036] This embodiment is carried out in a 30-liter polyester pilot plant and comprises the following steps:
[0037] (1) PTA 7110g, EG 1327g, isosorbide 1565g, CHDM 3088g, germanium dioxide 4.5g, sodium acetate 3g were placed in a reaction kettle in sequence, stirred evenly, and then pressurized to 2kg / cm with nitrogen. 2 Then the temperature is raised to 220°C, and the esterification reaction begins at about 220°C, that is, the temperature is gradually raised from 220°C to 255°C for 240 minutes, until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0038] (2) adding 50 g of antioxidant 1076 to the material obtained in step (1), continuing stirring, and evacuating to 75 Pa, then gradually heating to 255° C., and then gradually heating to 265° C. while maintaining a vacuum degree of 75 Pa, and performing polymerization reaction for 100 min until the intrinsic viscosity of the material reaches 0.538, and then stopping the reaction;
[0039] (3) The material obtained in step (2) is transported to a pelletizer to be cut into slices.
[0040] The obtained slices were analyzed for glass transition temperature (Tg) by differential scanning calorimetry (DSC), their intrinsic viscosity (IV) was measured by Ubbelohde viscometer, and their brightness and color (L, a, b) were analyzed by spectrophotometer. These data are listed in Table 1 for comparison.
[0041] Example 2
[0042] This embodiment is carried out in a 30-liter polyester pilot plant and comprises the following steps:
[0043] (1) PTA 7110 g, EG 1327 g, isosorbide 1565 g, CHDM 3088 g, germanium dioxide 4.5 g, sodium acetate 3 g and an appropriate amount of toner (selected from cobalt acetate, blue oil, red oil and purple oil) were placed in a reaction kettle in sequence, stirred evenly and pressurized with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220°C, and the esterification reaction begins at about 220°C, that is, the temperature is gradually raised from 220°C to 255°C for 240 minutes, until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0044] (2) adding 60 g of antioxidant 1076 and 1.55 g of phosphoric acid to the material obtained in step (1), continuing stirring, and evacuating to 75 Pa, then gradually heating to 255° C., and then gradually heating to 265° C. while maintaining a vacuum degree of 75 Pa, and performing polymerization reaction for 100 min until the intrinsic viscosity of the material reaches 0.65, and then stopping the reaction;
[0045] (3) The material obtained in step (2) is transported to a pelletizer to be cut into slices.
[0046] The obtained slices were analyzed for glass transition temperature (Tg) by differential scanning calorimetry (DSC), their intrinsic viscosity (IV) was measured by Ubbelohde viscometer, and their brightness and color (L, a, b) were analyzed by spectrophotometer. These data are listed in Table 1 for comparison.
[0047] Example 3
[0048] This embodiment is carried out in a 30-liter polyester pilot plant and comprises the following steps:
[0049] (1) PTA7110g, EG 1327g, isosorbide 1565g, CHDM 3088g, germanium dioxide 4.5g, sodium acetate 3g, phosphoric acid 1.55g, antioxidant 1076 20g, TBHQ 2g and an appropriate amount of toner (selected from cobalt acetate, blue oil, red oil and purple oil) were placed in a reaction kettle in sequence, stirred evenly and pressurized with nitrogen to 2kg / cm 2Then the temperature is raised to 220°C, and the esterification reaction begins at about 220°C, that is, the temperature is gradually raised from 220°C to 255°C for 240 minutes, until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0050] (2) Continue stirring the material obtained in step (1), and evacuate to 75 Pa, then gradually raise the temperature to 255° C., and then gradually raise the temperature to 265° C. while maintaining a vacuum degree of 75 Pa, and perform a polymerization reaction for 100 min until the intrinsic viscosity of the material reaches 0.65, and then stop the reaction;
[0051] (3) The material obtained in step (2) is transported to a pelletizer to be cut into slices.
[0052] The obtained slices were analyzed for glass transition temperature (Tg) by differential scanning calorimetry (DSC), their intrinsic viscosity (IV) was measured by Ubbelohde viscometer, and their brightness and color (L, a, b) were analyzed by spectrophotometer. These data are listed in Table 1 for comparison.
[0053] Example 4
[0054] This embodiment is carried out in a 30-liter polyester pilot plant and comprises the following steps:
[0055] (1) PTA7110g, EG 540g, isosorbide 2220g, CHDM 3088g, germanium dioxide 6g, sodium acetate 3g, phosphoric acid 1.55g, antioxidant 1010 13g, AT626 26g were placed in a reactor in sequence, stirred evenly, and then pressurized to 2kg / cm with nitrogen. 2 Then the temperature is raised to 220°C, and the esterification reaction begins at about 220°C, that is, the temperature is gradually raised from 220°C to 255°C for 240 minutes, until the top temperature of the esterification tower is less than 70°C, and the esterification is completed;
[0056] (2) Continue stirring the material obtained in step (1), and evacuate to 75 Pa, then gradually raise the temperature to 255° C., and then raise the temperature to 265° C. while maintaining a vacuum degree of 75 Pa, and carry out polymerization reaction for 100 min until the intrinsic viscosity of the material reaches 0.65, and then stop the reaction;
[0057] (3) The material obtained in step (2) is transported to a pelletizer to be cut into slices.
[0058] The obtained slices were analyzed for glass transition temperature (Tg) by differential scanning calorimetry (DSC), their intrinsic viscosity (IV) was measured by Ubbelohde viscometer, and their brightness and color (L, a, b) were analyzed by spectrophotometer. These data are listed in Table 1 for comparison.
[0059] Table 1
[0060] Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Tg 93 91 91 93 105 IV 0.536 0.538 0.648 0.652 0.612 L 52.3 56.6 47.4 49.4 53.9 a -1.2 -1.6 -1.2 -0.6 -1.7 b 10.2 6.3 2.6 0.7 6.8
[0061] As can be seen from Table 1 above, Examples 3 and 4 are the best. Example 3 can withstand temperatures exceeding 90°C, and Example 4 can withstand Affected by temperatures exceeding 100°C.
[0062] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A high-brightness, high-white, high-temperature-resistant modified copolyester material, characterized by: The invention is prepared by esterification and polymerization of raw material components including terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate and an antioxidant, wherein the antioxidant is a phenolic antioxidant and / or a phosphite antioxidant. The mass ratio of terephthalic acid, ethylene glycol, isosorbide and 1,4-cyclohexanedimethanol is 70-72:13-14:15-16:30-31; the added amount of germanium dioxide is 50-500ppm, the added amount of sodium acetate is 10-500ppm, and the added amount of antioxidant is 100-6000ppm.
2. A high-brightness, high-white, high-temperature-resistant modified copolyester material as claimed in claim 1, characterized in that: The raw material components also include phosphoric acid, which is added in an amount of 10-200 ppm.
3. A high-brightness, high-white, high-temperature-resistant modified copolyester material as claimed in claim 2, characterized in that: The raw material components also include a toner.
4. A high-brightness, high-white, high-temperature-resistant modified copolyester material as claimed in claim 3, characterized in that: The toner includes cobalt acetate, blue oil, red oil and purple oil.
5. A high-brightness, high-white, high-temperature-resistant modified copolyester material according to any one of claims 1 to 4, characterized in that: The phenolic antioxidant includes at least one of antioxidant 1076, antioxidant 1010 and TBHQ; the phosphite antioxidant is AT626.
6. The method for preparing the high-brightness, high-whiteness, high-temperature-resistant modified copolyester material according to claim 1 or 5, characterized in that: The steps include: (1) Place terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide and sodium acetate into a reactor, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed; (2) After adding an antioxidant to the material obtained in step (1), stirring is continued, and vacuum is applied to carry out polymerization reaction at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and the reaction is stopped.
7. The method for preparing the high-brightness, high-whiteness, high-temperature-resistant modified copolyester material according to claim 2 or 5, characterized in that: The steps include: (1) Put terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate, antioxidant and phosphoric acid into a reactor, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed; (2) Continue stirring the material obtained in step (1), evacuate the mixture, and carry out polymerization reaction at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and then stop the reaction.
8. The method for preparing the high-brightness, high-whiteness, high-temperature-resistant modified copolyester material according to any one of claims 3 to 5, characterized in that: The steps include: (1) Place terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate and toner into a reaction kettle, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed; (2) adding an antioxidant and phosphoric acid to the material obtained in step (1), continuing to stir, evacuating, and polymerizing at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and then stopping the reaction; Or include the following steps: (1) Put terephthalic acid, ethylene glycol, isosorbide, 1,4-cyclohexanedimethanol, germanium dioxide, sodium acetate, antioxidant, phosphoric acid and toner into a reaction kettle, stir evenly and pressurize with nitrogen to 2 kg / cm 2 Then the temperature is raised to 220-255°C for esterification reaction until the top temperature of the esterification tower is less than 70°C, and the esterification is completed; (2) The material obtained in step (1) is continued to be vacuumized and polymerized at 255-265° C. until the intrinsic viscosity of the material reaches 0.6-0.7, and the reaction is stopped.
Citation Information
Patent Citations
Process for preparing an azo dye.
CH107620A